Power and domination relationships in match fixing networks in Portuguese professional football - Cima, C. (Trends in Organized Crime, 2025)
This paper uses Pires’ (Sociologia Problemas E Práticas 100:41–63. 2022) analytical framework to analyse the power and domination relationships that govern the betting related match-fixing practices in Portuguese professional football. The analysis focuses on the “Jogo Duplo” (Double Game) prosecution order - the first and thus far the only Portuguese betting related match-fixing case tried in court - and on semi-structured interviews with two professional football players who were approached to fix matches by the so-called “Luso-Malaysian” group. Contrary to the realities of other countries which dictate the institutional discourse, the Portuguese case exposes a organised transnational criminal group established upon opportunities and characterised by amateurism and disloyalty, and in which the power dynamics are determined by the possession and structured allocation of a scarce material resource (money). In Portuguese professional football, threats seem to play a minor role in inducing football players to fix matches or in preventing reports. While the offer of bribes constituted the mandatory material resource to make the corrupt pacts viable, the use of moral and communicational resources was configured as a complementary mechanism to persuade the most undecided players. This research shows that in organised crime groups with a low level of sanctions, the players can refuse to participate in the game, adopt infidelity acts, or even decide to leave the game halfway through without experiencing resistance and conflict.